Corporate cultures : the rites and rituals of corporate life - Deal, Terrence E.; Kennedy, Allan A. (Cambridge, Massachusetts : Perseus Books, 2000)
For junior and senior managers alike, Deal and Kennedy offer guidelines for diagnosing the state of one's own corporate culture and for using the power of culture to wield significant influence on how business gets done.
Part I: Cultures. 1. Strong cultures: the new "old rule" for business success -- 2. Values: the core of the culture -- 3. Heroes: the corporate right stuff -- 4. Rites and rituals: culture in action -- 5. Communications: working the cultural network -- Part II: Putting cultures into practice. -- 6. Corporate tribes: identifying the cultures -- 7. Diagnosis: learning to read cultures -- 8. Symbolic managers: managing the culture -- 9. Change: reshaping cultures -- 10. Cultures of the future: the atomized organization.
"A classic reissued with a new introduction by the authors"--Cover Originally published: Reading, Mass. : Addison-Wesley, ©1982
Includes bibliographical references and index.
Keywords: CORPORATIONS